Turkic elements in the toponymy of South Ossetia - Yu.A. Dzitstsojty (Ученые записки Казанского университета: Серия Гуманитарные науки)
In this paper, the Turkic elements in the toponymy of South Ossetia were analyzed. Most of these elements have never been previously studied. A brief survey of the history of the study of Turkisms in the toponymy of the region was performed. It was revealed that the proportion of South Ossetian Turkisms is very insignificant: they account for less than 1% of the total number of toponyms of South Ossetia. Here, it should be emphasized that the study of South Ossetian toponymy and, in particular, Turkisms is at the early stage and, therefore, other Turkisms may be discovered in the future. In the toponymy of North Ossetia, there are many more Turkisms, which is explained by the direct Ossetian-Turkic contacts in the North Caucasus without the participation of the ancestors of South Ossetians. A total of 20 toponyms, all borrowed from the Turkic languages, were analyzed. These are mainly names associated with livestock life, as well as names reflecting the realities of mountain landscapes and water objects. The identified Turkisms in the toponymy of South Ossetia, with rare exceptions, do not occur in the toponymy or dialects of North Ossetia, thereby indicating their independent appearance due to the partial infiltration of the Turkic ethnic element into the territory of South Ossetia.